Choosing the right thing to do : in life, at work, in relationships, and for the planet - Shapiro, David A., 1957- (Berrett-Koehler, 1999)
The author of "Repacking your bags" offers a thoughtful examination of how people make choices and offers lessons for creating a valuable moral legacy.